Bilateral talon cusps $rowena V. Maunahan. - Maunahan, Rowena V.
Clinical problems that may arise because of the talon cusps include stagnation of food debris, caries-susceptible developmental grooves, soft tissue irritation, esthetics, occlusal interference, periapical lesions and problems in diagnosis and clinical management for dentists.
This case involves an 11 year old health boy who consulted the Pediatric Dentistry Division for routine check-up. On examination, a bilateral talon cusp on the palatal surface of the maxillary right and left incisor was revealed. This case was classified as Type 1. The treatment done were pulpotomy and direct pulp cupping. Follow up examination after 2 months showed no adverse symptoms. Periapical readiograph indicated a normal periapex.
Keywords: Talon cusps; Pulp capping